Estabilidade global de estruturas associadas: influência de elementos estruturais em concreto armado na rigidez de um edifício em estruturas metálicas - Santos, Rafael Rosa dos (2021)
The emergence of new building systems, such as those usingmixed steel and concrete elements, is strongly linked to the development of reinforced concrete and steel structures. The increasing technological development and industrialization of the construction industry in the current market are driven by the emergence of these new structural systems. The industrialization of the construction industry, as well as the joint work of steel and concrete materials, has been a very effective structural solution used nowadays. This course conclusion paper proposes a study of the global stability of a multi-story mixed structure building, aiming to analyze the effect of structural elements of reinforced concrete in a purely metallic structure, without bracing elements, to reduce as much as possible, the horizontal displacements and their second-order effects, as this analysis is indispensable as the slenderness of the structures increases.